Of Meat and Manhood - Zachary A. Kramer (Washington University Law Review, 2011)
The idea that “real” men eat meat is firmly embedded in our culture. For those men who are benefited by the stereotype, eating meat serves as a confirmation of their manhood, a kind of marker of their privileged status as masculine men. This is not the case for men who do not eat meat. In our culture, a man who does not eat meat is often seen as insufficiently masculine. In this Article, I use the relationship between meat and manhood as a springboard to challenge the way in which employment discrimination law—more specifically, Title VII of the Civil Rights Act —conceives of sex discrimination. The Article focuses in particular on what is perhaps the most transformative theory of sex discrimination—the gender-stereotyping theory of sex discrimination. The thrust of the gender-stereotyping theory is that an employer cannot discriminate against an employee for failing to conform to stereotypical gender expectations. The Supreme Court announced the theory in 1989, in the seminal case Price Waterhouse v. Hopkins. In doing so, the Court ushered in a new wave of sex discrimination claims, shifting the focus of Title VII’s sex discrimination project from formal sex segregation to more subtle forms of discrimination concerning how employees look and behave in the workplace.
Keywords: Price Waterhouse v. Hopkins 490 U.S. 228 (1989); Employment discrimination; Sex discrimination; Sexual stereotypes; Civil Rights Act of 1964; United States